Information technologies that facilitate care coordination: provider and patient perspectives. Issue 3 (23rd May 2018) - Dixon, Brian E; Embi, Peter J; Haggstrom, David A
Abstract: Health information technology is a core infrastructure for the chronic care model, integrated care, and other organized care delivery models. From the provider perspective, health information exchange (HIE) helps aggregate and share information about a patient or population from several sources. HIE technologies include direct messages, transfer of care, and event notification services. From the patient perspective, personal health records, secure messaging, text messages, and other mHealth applications may coordinate patients and providers. Patient-reported outcomes and social media technologies enable patients to share health information with many stakeholders, including providers, caregivers, and other patients. An information architecture that integrates personal health record and mHealth applications, with HIEs that combine the electronic health records of multiple healthcare systems will create a rich, dynamic ecosystem for patient collaboration. Abstract : Provider-centered electronic health records are more widely adopted than patient-centered technologies in health care systems. Personal health records, mHealth applications, health information exchanges, and electronic health records together will create a dynamic health information ecosystem centered around patients.